THE EFFECT OF E-COMMERCE, ENTREPRENEURSHIP ORIENTATION AND MARKET ORIENTATION ON BUSINESS PERFORMANCE - Valentino, Wilsen; Handoyo, Sarwo Edy (International Journal of Application on Economics and Business, 2023)
MSMEs have an important role in the Indonesian economy. It is necessary to know the factors that affect the performance of SMEs. The purpose of this research is to test empirically the effect of e-commerce, market orientation, and entrepreneurial orientation on MSME business performance. The research method used is the quantitative method. The population in this study are the owners of MSME Ayam Geprek di Jakarta. The sampling technique uses the purposive sampling method. The Source of data used is primary data. The data analysis tool used was regression analysis which was processed using Partial Least Squares Structural Equation. The results of this study indicate that e-commerce has a positive and significant effect on business performance. Market orientation has a positive but insignificant effect on business performance. Entrepreneurial orientation has a positive and significant effect on business performance.